Analisis Undang-Undang Lalu Lintas Terhadap Maraknya Penggunaan Knalpot Brong dan Tingkat Kepatuhan Masyarakat Purbalingga - Narendo, Virgiawan Moro (UM Purwokerto Press, 2024)
Doing modifications to a vehicles has become a common thing for people to do, one of the modifications is changing the standard exhaust to a loud exhaust. In fact, the use of exhausts that exceed the sound threshold has been regulated in Law Number 22 of 2009 concerning Road Traffic and Transportation. Based on that information, this research will discuss law enforcement for loud exhaust users from the Purbalingga Police Traffic Unit and the obstacles in enforcing these regulations. This research was conducted using a juridical-empirical method by conducting observations and interviews with related parties. The Purbalingga Traffic Police have taken preventive action to implement Article (12) letter G of Law No. 22 of 2009 and also repressive action in the form of fines, confiscation and even criminal penalties. Meanwhile, the obstacle faced by Purbalngga Traffic Police is the lack of public knowledge about the rules for using Brong exhaust.